Family identity in the era of Covid-19 - García Lirios, Cruz (Facultad de Trabajo Social y Desarrollo Humano, 2022)
One settled down the validity and trustworthiness of a scale to measure the familiar identity around the member health of one of its patient. Three factors referred to the familiar leadership settled down, the transition to the leadership and the absence of leadership. A model of multiple linear regression was elaborated to demonstrate the causal relation between the three factors on the regional identity. Finally, through another structural model the effect of other valuing, actitudinales, intentional and behavioral variables was inferred and discussed perceptual, not including in the model.